Constituent power, violence, and the state - Vouros, Dimitri, author.
1 online resource.
Keywords: "In Constituent Power, Violence, and the State, Dimitri Vouros examines the question of political violence by placing the thought of Georges Sorel, Walter Benjamin, and Hannah Arendt in conversation with contemporary theories of sovereignty and constituent power. Vouros argues that the violence sustaining the modern state inhibits institutional accountability and derails constituent power. The paradox of modern law-which is both the expression of the people's will but also alienated from them-sets the stage for political contestation. For Vouros, the multitude's potentiality is actualized through either organized or spontaneous acts of resistance against state force. Antagonism is therefore a key element of the political and must be included in any theory of political agonism. A strong notion of constituent power ensures the integrity of the public sphere and the expansion of citizens' political agency. Bringing all these ideas together is unique for this field of investigation. Accessible and engagingly written, Constituent Power, Violence, and the State is a must read for researchers in political theory and political philosophy. Critical legal studies scholars and social theorists will also profit from this book"--